ANALYSIS OF THE MICROSERVICE ARCHITECTURE OF THE SMART CITY - DMYTROTSA, LESIA; PALKA, OLEH (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Recently, the concept of "Smart Cities" has been significantly improved along with the growth and development of the Internet of Things as a new form of sustainable development. Smart cities rely on an independent and distributed infrastructure that includes information processing and management systems, a diverse network infrastructure, and a sensitivity that includes millions of information sources. However, due to the ever-increasing amount of data and the number of connected IoT devices, issues such as high latency, bandwidth barriers, security and privacy, and scalability are the result of the ongoing construction of a smart city network. Developing an efficient, secure, and scalable distributed architecture by bringing computer resources and storage closer to the endpoint is necessary to overcome the limitations of today’s smart city network. There are many types of smart services that aim to automate and perform repetitive routine tasks. In addition, they come in different forms depending on the city’s population, culture, including the level of awareness of citizens, geography, and schedule. Not to mention, on a micro-technical level, they tend to create large data sets with fast continuous execution, thus falling into the category of big data, and therefore can be a source of analytical data. Microservice architectures are born as a solution to this problem. By implementing a single small function that is confined to a running process, independent microservices can be deployed separately in a distributed system. In the context of mobility in a smart city, a service meets the need of a citizen who needs to move from one part of the city to another or provides useful information for the same purpose. In this article, we demonstrate how microservice architecture can be used to create IoT services for multimobility in a smart city.